Perverse effects of two-tier wage bargaining structures - Tito Boeri (IZA World of Labor, 2015)
Debate over labor market flexibility focuses mainly on firing costs, while largely ignoring wage determination and the need for collective bargaining reform. Most countries affected by the euro debt crisis have two-tier bargaining structures in which plant-level bargaining supplements national or industrywide (multi-employer) agreements, taking the pay agreement established at the multi-employer level as a floor. Two-tier structures were intended to link pay more closely to productivity and to allow wages to adjust downward during economic downturns, while preventing excessive earning dispersion. However, these structures seem to fail precisely on these grounds.
Keywords: J3; J5; J52; 330; wage drift; favorability principle; productivity-related pay; multi-employer bargaining